Euclidean preferences, option sets and strategyproofness - Georges Bordes; Gilbert Laffond; Michel Le Breton (SERIEs - Journal of the Spanish Economic Association, 2011)
In this note, we use the technique of option sets to sort out the implications of coalitional strategyproofness in the spatial setting. We also discuss related issues and open problems.
Keywords: D71; D72; D78; 330; social choice; strategyproofness; voting; Politische Entscheidung; Abstimmungsregel; Neue politische Ökonomie; Theorie